2005
DOI: 10.1002/cne.20804
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic connectivity in the midget‐parvocellular pathway of primate central retina

Abstract: The synaptic connectivity of OFF midget bipolar cells was investigated in the central retina of two primate species, the New World common marmoset monkey, Callithrix jacchus, and the Old World macaque monkey, Macaca fascicularis. In marmosets, dichromatic and trichromatic animals were compared. Bipolar output synapses were identified with antibodies against ribbon proteins (kinesin, C-terminal binding protein 2) or with an antiserum that recognizes postsynaptic glutamate receptor clusters (GluR4). The midget b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 49 publications
6
85
0
Order By: Relevance
“…It has been suggested that the midget bipolar cells in the central macaque retina show further color selectivity, such that M-cone-contacting midget bipolar cells make different numbers of synapses with midget ganglion cells than L-cone-contacting midget bipolar cells (Calkins et al, 1994). However, we showed recently that the number of synapses made by FMB cells is comparable in dichromat and trichromatic animals (Jusuf et al, 2006), so the differences found by Calkins et al (1994) may not be necessarily related to trichromatic color vision. Here, we found that the mosaic of FMB axon terminals in the peripheral retina is spatially independent of the midget ganglion cell mosaic.…”
Section: Selective Wiring In the Primate Retina?mentioning
confidence: 50%
See 2 more Smart Citations
“…It has been suggested that the midget bipolar cells in the central macaque retina show further color selectivity, such that M-cone-contacting midget bipolar cells make different numbers of synapses with midget ganglion cells than L-cone-contacting midget bipolar cells (Calkins et al, 1994). However, we showed recently that the number of synapses made by FMB cells is comparable in dichromat and trichromatic animals (Jusuf et al, 2006), so the differences found by Calkins et al (1994) may not be necessarily related to trichromatic color vision. Here, we found that the mosaic of FMB axon terminals in the peripheral retina is spatially independent of the midget ganglion cell mosaic.…”
Section: Selective Wiring In the Primate Retina?mentioning
confidence: 50%
“…Dye injections were performed as described previously (Szmajda et al, 2005;Jusuf et al, 2006). Briefly, animals were anesthetized with isofluorane (Forthane; Abbott, Sydney, Australia; ICI, 1-2%) and intramuscular ketamine (30 mg/kg) and xylazine hydrochloride (Rompun; Bayer Animal Health Australia, Pymble, New South Wales, Australia; 2-4 g/kg).…”
Section: Retrograde Labeling Of Retinal Ganglion Cells In Marmosetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most foveal PC cells derive input from a single L or M cone via a single midget bipolar cell (Kolb and Dekorver, 1991;Calkins et al, 1994;Jusuf et al, 2006a) and thus should get a dominant functional input to the receptive field center from a single cone type. Under the "random wiring" hypothesis (Mollon et al, 1984;Shapley and Perry, 1986;Lennie et al, 1991), this one-to-one connectivity is the dominant source of spectral bias in PC fields and thus produces the afferent signals serving red-green color vision.…”
Section: Introductionmentioning
confidence: 99%
“…Each midget bipolar cell makes dominant contact with a single midget ganglion cell in the inner plexiform layer. Again in the fovea there is one-to-one connectivity giving a 'private line' for signals from each foveal cone (Jusuf, Martin, & Grünert, 2006a).…”
Section: Cone Pathways In the Foveamentioning
confidence: 99%